āl-Irhāb āl-Ijrāmiy fi Bandung fi āl-Akhbār āl-'Arābiyāh ālā āl-Intirnit; Istinādān ilā tāhlil āl-Khithāb ān-Naqdiy li Theo Van Leeuwen - Lulu Eka Aprilia; Achmad Diny Hidayatullah (Mantiqu Tayr: Journal of Arabic Language, 2024)
The mass media plays a crucial role in shaping public opinion and influencing people's perceptions of important issues being discussed, one of which is terrorism. This research aims to identify and analyze critical discourse through exclusion strategies and inclusion strategies and describe the three Arab online media in constructing news. This research uses a critical discourse analysis approach from Theo van Leeuwen's perspective. Researchers used qualitative methods with content analysis techniques from Arabic online media, namely al Arabiya.net, al Jazeera.net, and okaz.com.sa with the theme of Indonesian criminal terrorism news namely Suicide Bombing in Bandung December 7, 2022 edition. The collection technique uses the documentation, observation, and record method. The results of the research show that the exclusion strategy is used in the media al Arabiya.net with 2 data and al Jazeera.net with 1 data, and the inclusion strategy is used in the media al Arabiya.net 6 models, al Jazeera.net 7 models, and okaz.com.sa as many as 5 data models. The three online media have a tendency towards groups or government agencies rather than terrorists. Furthermore, suggestions for further research use the theory of media psychology and emotional effects.